Innovation educational activities as a prerequisite for quality training of future lawyers - Головко, Світлана Григорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article analyzes a problem of innovative technologies implementation into teaching of law students. The main methods and forms of intensification of teaching and learning activity of future lawyers as a necessary condition of the professional competence formation are analyzed. The idea that the effectiveness of the training of future lawyers depends on a complex of pedagogical conditions, including those productive methods and technologies that provide achievement of targeted educational goals, and obtaining of educational content according to national and European standards and principles of quality assurance, taking into account the requirements of the labor market, is substantiated. The basic didactic requirements that ensure successful implementation of interactive teaching (organization of educational process as a comprehensive, partnership, intensive communication; creating a favorable, positive psychological atmosphere in the training collective; special organization of educational space) were analyzed. The influence of interactive learning on the development of professional competence is investigated. In particular, through fundamentalization and professional orientation of teaching, attention is drawn to a stable need in constant self-education and lifelong learning, development of skills and abilities to concentrate and effectively use with the aim to solve non-standard problems of professional activities received in learning process knowledge. Specific features of the organization of active teaching in which students are involved in the most productive cognitive activity, express independence and creativity in solving of educational problems are shown. Attention is also paid to the important characteristics of interactive teaching as a permanent active cooperation of all subjects of the educational process. Its influence on quality changes of a role of a teacher from a source of correct knowledge to a coordinator of corporate teaching and learning activities of students is grounded. The practical experience of situational modeling using as one of the types of interactive teaching in training of future lawyers is summarized. Its purpose is to acquire skills by students to participate in activities of public institutions, which is connected with their future professional activities, and also procedures of making of decision.